Effects of cancer treatment on household impoverishment: a multicentre cross-sectional study in China. Issue 6 (30th June 2021) - Fu, Wenqi; Shi, Jufang; Zhang, Xin; Liu, Chengcheng; Sun, Chengyao; Du, Yupeng; Wang, Hong; Liu, Chaojie; Lan, Li; Zhao, Min; Yang, Li; Bao, Burenbatu; et al.
Abstract : Objectives: To determine the incidence and intensity of household impoverishment induced by cancer treatment in China. Design: Average income and daily consumption per capita of the households and out-of-pocket payments for cancer care were estimated. Household impoverishment was determined by comparing per capita daily consumption against the Chinese poverty line (CPL, US1.2) and the World Bank poverty line (WBPL, US1.9) for 2015. Both pre-treatment and post-treatment consumptions were calculated assuming that the households would divert daily consumption money to pay for cancer treatment. Participants: Cancer patients diagnosed initially from 1 January 2015 to 31 December 2016 who had received cancer treatment subsequently. Those with multiple cancer diagnoses were excluded. Data sources: A household questionnaire survey was conducted on 2534 cancer patients selected from nine hospitals in seven provinces through two-stage cluster/convenience sampling. Findings: 5.89% (CPL) to 12.94% (WBPL) households were impoverished after paying for cancer treatment. The adjusted OR (AOR) of post-treatment impoverishment was higher for older patients (AOR=2.666–4.187 for ≥50 years vs <50 years, p<0.001), those resided in central region (AOR=2.619 vs eastern, p<0.01) and those with lower income (AOR=0.024–0.187 in higher income households vs the lowest 20%, p<0.001). The patients without coverage from social health insurance had higher OR (AOR=1.880, p=0.040) of experiencing post-treatment household impoverishment than those enrolled with the insurance for urban employees. Cancer treatment is associated with an increase of 5.79% (CPL) and 12.45% (WBPL) in incidence of household impoverishment. The median annual consumption gap per capita underneath the poverty line accumulated by the impoverished households reached US128 (CPL) or US212 (WBPL). US31 170 395 (CPL) or US115 238 459 (WBPL) were needed to avoid household impoverishment induced by cancer treatment in China. Conclusions: The financial burden of cancer treatment imposes a significant risk of household impoverishment despite wide coverage of social health insurance in China.